Growth hormone receptor promotes osteosarcoma cell growth and metastases - Mo Cheng; Wending Huang; Weiluo Cai; Meng Fang; Yong Chen; Chunmeng Wang; Wangjun Yan (FEBS Open Bio)
Osteosarcoma (OS) is the primary bone malignancy in children and adolescents, with a high incidence of lung metastasis and poor prognosis. Here, we report that growth hormone receptor (GHR) is overexpressed in OS samples compared with osteofibrous dysplasia. We subsequently demonstrated that GHR knockdown inhibited colony formation, promoted cell apoptosis and decreased the number of cells at G2/M phase in 143B and U2OS cells. Furthermore, knockdown of GHR inhibited tumor growth in vivo. Together, these findings indicate that GHR modulates cell proliferation and metastasis through the phosphoinositide 3‐kinase/AKT signaling pathway and may be suitable for use as a putative biomarker of OS.